Exploring of optimum paces of "Uchikomi (repetition trainings)" for foot techniques toward enhancing endurance capacity in collegiate male Judo athletes - Masuchi, K.; Norikane, S.; Ogura, D.; Kubota, Y.; Matsui, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
The current Judo competition requires higher stamina than before the rule revision in 2017. Endurance capacity as a foundation of stamina is enhanced by training/conditioning composed of optimum relative exercise intensities associated with stress response, which is an important metabolic/endocrine system inducing biological adaptation. The repetition training of Judo techniques (Uchikomi) for shoulder throw (Seoi-nage) as a typical hand technique (Te-waza) induces blood lactate elevation and stress response at faster pace than 1 trial/1.5 sec (20 trials/30 sec), which is theoptimum pace for Seoi-nage Uchikomi enhancing endurance capacity. However, optimum paces of Uchikomi for foot techniques (Ashi-waza such as Uchi-mata, Osoto-gari, and Ouchi-gari), which are much popular techniques than hand techniques, remain untested. To address this issue, collegiate male Judo athletes participated in this study, and were measured psychological, physiological, and biochemical parameters during a pace-incremental repetition training for foot techniques. The borg-scale,heart rate, and estimated oxygen consumption increased in a repetition pace-dependent manner in all techniques. Blood lactate levels unchanged at a slow repetition pace but started to elevate at 1 trial/1.25 sec of pace (24 trials/30 sec) in Osoto-gari, 1 trial/1.0 sec of pace (30 trials/30 sec) in Uchi-mata, and 1 trial/0.85 sec of pace (35 trials/30 sec) in Ouchi-gari, respectively. At maximal repetition pace, blood lactate levels neared or exceeded 10 mM, and plasma adrenocorticotropic hormone (ACTH) levels, a stress marker, increased in all techniques. Our findings providemetabolic/endocrine evidence for optimum paces of repetition trainings for foot techniques toward improving endurance capacity, which are ? 1 trial/1.25 sec in Osotogari,? 1 trial/1.0 sec in Uchi-mata, and ? 1 trial/0.85 sec in Ouchi-gari, respectively. This experimental protocol and perspective on relative intensity with metabolic/endocrine parameters in Judo movements ultimately contributes to better training/conditioning programs for Judo-specific stamina.